2018
DOI: 10.4196/kjpp.2018.22.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in adenosine pharmacological preconditioning-induced cardioprotection

Abstract: Adenosine is a naturally occurring breakdown product of adenosine triphosphate and plays an important role in different physiological and pathological conditions. Adenosine also serves as an important trigger in ischemic and remote preconditioning and its release may impart cardioprotection. Exogenous administration of adenosine in the form of adenosine preconditioning may also protect heart from ischemia-reperfusion injury. Endogenous release of adenosine during ischemic/remote preconditioning or exogenous ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
0
18
0
2
Order By: Relevance
“…Previous studies have demonstrated that mitochondrial KATP channel activity and adenosine signaling exert a protective effect during IRI 9,35,36,51 . Induction of these molecular routes exert an immunomodulatory and anti-oxidant effect in different models of IRI [52][53][54][55] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have demonstrated that mitochondrial KATP channel activity and adenosine signaling exert a protective effect during IRI 9,35,36,51 . Induction of these molecular routes exert an immunomodulatory and anti-oxidant effect in different models of IRI [52][53][54][55] .…”
Section: Discussionmentioning
confidence: 98%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Treatment with 5-HD or 8-SPT abolishes the protective effect of conditioning. Earlier studies have shown that administering the KATP channel blocker 5-HD or the non-selective adenosine inhibitor 8-SPT, eliminates the protective effect of IPre and IPost 35,36 . To decipher the role of mitochondrial KATP channel activity and adenosine signaling in this context, we administered 5-HD or 8-SPT before the application of suprarenal abdominal artery occlusion and reperfusion (Fig.…”
Section: Conditioning Reduces the Accumulation Of Dna Damage In Kidnementioning
confidence: 99%
“…Directly acting, potent agonists (1-15) and antagonists (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) for each of the ARs are available as pharmacological probes, and, in several cases, agents approved for human use ( Figure 2) [22]. AR agonists 1 (adenosine) and 9 (regadenoson) and are approved for clinical use in myocardial perfusion diagnostics and/or supraventricular tachycardia diagnosis and treatment.…”
Section: Known Ar Ligandsmentioning
confidence: 99%
“…Ischemic preconditioning of the heart, i.e., when short ischemic episodes improve the outcome of a subsequent ischemia event, is thought to involve ARs, consistent with the highly elevated levels of adenosine that occur in hypoxia. Preconditioning can also be induced by exogenous AR agonists, potentially through activation of each of the four AR subtypes, which are present on cardiac myocytes [34,35]. Adenosine pretreatment also conditions against ischemic cardiac damagẽ 24-72 h later [36].…”
Section: Vasoactive and Other Cardiovascular Effectsmentioning
confidence: 99%
“…Ischemic preconditioning of the heart, when a pretreatment improves the outcome from an ischemia event, is thought to involve ARs, consistent with the highly elevated levels of adenosine that occur in hypoxia. Preconditioning can also be induced by exogenous AR agonists, potentially through activation of each of the four AR subtypes, which are present on cardiac myocytes (Cohen et al, 2010;Singh et al, 2018;Wan et al, 2019). Adenosine pretreatment also conditions against ischemic cardiac damage ~24-72 hours later (Baxter, 2002).…”
Section: Vasoactive and Other Cardiovascular Effectsmentioning
confidence: 99%